2008
DOI: 10.1007/978-0-387-09684-1_21
|View full text |Cite
|
Sign up to set email alerts
|

Archetypal Internet-Scale Source Code Searching

Abstract: Programmers often search for Open Source code to use in their projects. To understand how and why programmers search for source code, we conducted a web-based survey and collected data from 69 respondents, including 58 specific examples of searches. Analyzing these anecdotes, we found that they could be categorized along two orthogonal dimensions: motivation (reuse vs. reference example) and size of search target. The targets of these searches could range in size from a block (a few lines of code) to a subsyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 3 publications
0
22
0
Order By: Relevance
“…While there are a few studies outside the scope of this review focusing on software selection [46,56,105,184] and knowledge sharing within OSS communities [119,173,195], none of these are directed towards studying actual practice in organizations. A few studies have started to look at some of the challenges in the borderlands between integrating an OSS component and contributing to the development of it [106,130,186], but further research is needed to solve the maintenance challenges facing developers who integrate a large number of components into their products.…”
Section: Topics For Future Researchmentioning
confidence: 99%
“…While there are a few studies outside the scope of this review focusing on software selection [46,56,105,184] and knowledge sharing within OSS communities [119,173,195], none of these are directed towards studying actual practice in organizations. A few studies have started to look at some of the challenges in the borderlands between integrating an OSS component and contributing to the development of it [106,130,186], but further research is needed to solve the maintenance challenges facing developers who integrate a large number of components into their products.…”
Section: Topics For Future Researchmentioning
confidence: 99%
“…Hoffmann et al [24] showed that when developers search the Web, the majority of their queries are about APIs. Other studies of developers' needs and practices have shown that developers seek and use code examples to learn APIs [35,32,39,34,36,44].…”
Section: Introductionmentioning
confidence: 99%
“…This general impression is clearly backed-up by the recent online survey conducted by Umarji et al [11] who identified nine archetypal groups of source code searches amongst 58 anecdotes of how developers typically use source code search engines. Eight of these nine archetypes deal with reuse and the authors were able to distinguish four subgroups of searches for reusable code from four subgroups with searches for reference examples that are supposed to deliver some inspiration for how to implement some given programming task.…”
Section: Related Workmentioning
confidence: 95%
“…The developer makes use of the search engine to support the design process of the component being developed and to get support in the early implementation phase. Speculative searches subsume methods like the design prompter (see below), or drawing inspiration from open source and library searches as described in [11]. Searches for reusable code snippets also identified in the cited source are the only small exception in this context as they typically only appear while developers are already coding.…”
Section: Speculative Searchesmentioning
confidence: 98%
See 1 more Smart Citation